Untangling the Tangle of Revenge Porn in the United States: A Comparative Study - Fernando, Zico Junius; Pase, Ana Tasia (Indonesian Comparative Law Review, 2024)
This research examines the phenomenon of revenge porn in the legal context of the United States and identifies important lessons for Indonesia. Using a multifaceted approach, this research explores legal definitions, sentencing, and protections for victims in various US states, as well as exploring the psychosocial impact of revenge porn on victims. This research utilizes normative legal methods by adopting statutory, conceptual, comparative, and futuristic approaches. The nature of this research is descriptive-prescriptive. The data that has been collected is analyzed using the content analysis method. The study found that there is significant variation in laws and approaches to handling revenge porn among states, reflecting differences in social values and legal priorities. For example, states such as California, New York, and Texas feature different definitions and penalties, as well as varying levels of protection for victims. Indonesia can draw valuable lessons from formulating its own legal strategy for this phenomenon. This research suggests the importance of specific legislation that clearly defines revenge porn, a flexible sentencing system that considers the context of individual cases, and strong psychosocial support for victims